Pharmacological inhibition of pigmentation in Cryptococcus. Issue 1 (10th November 2018) - Zimbres, Ana Claudia G; Reuwsaat, Julia C V; Barcellos, Vanessa A; Joffe, Luna S; Fonseca, Fernanda L; Staats, Charley C; Schrank, Augusto; Kmetzsch, Livia; Vainstein, Marilene H; Rodrigues, Marcio L
Abstract: Melanin formation is a promising target for antifungal development. We screened a collection of 727 compounds that were previously approved for clinical use in humans for inhibition of pigmentation in Cryptococcus gattii, a lethal fungal pathogen that causes damage to both immunocompetent and immunocompromised hosts. The pyrimidine analogues flucytosine (5-fluorocytosine [5-FC]), 5-fluorouracil (5-FU) and carmofur were identified as efficient inhibitors of pigmentation in the C. gattii model. Since melanin synthesis is enzymatically catalyzed by laccase in Cryptococcus, we investigated whether inhibition of pigmentation by the pyrimidine analogues was laccase-mediated. Enzyme activity and expression of LAC genes were not involved in the effects of the pyrimidine analogues, suggesting alternative cellular targets for inhibition of pigmentation. To address this hypothesis, we screened a collection of approximately 8000 mutants of C. gattii that were produced by insertional mutation after incubation with Agrobacterium tumefaciens and identified a gene product required for the anti-pigmentation activity of 5-FC as a beta-DNA polymerase. Reduced expression of this gene affected capsule formation and urease activity, suggesting essential roles in the cryptococcal physiology. These results demonstrate a previously unknown antifungal activity of 5-FC and reveal a promising target for the development of novel antifungals. Abstract : Melanin synthesis can be pharmacologically inhibited in the lethal pathogen Cryptococcus .